Efficacy and safety of salvianolate injection in treating acute myocardial infarction: a meta-analysis and systematic literature review - Chen, Pengfei; Zhang, He; Gao, Zhuye; Shi, Dazhuo; Zhang, Jie (Frontiers in Pharmacology, 2024)
PurposeSalvianolate for injection (SFI) is a widely used treatment for acute myocardial infarction (AMI). This study aims to assess the efficacy and safety of SFI in treating AMI by synthesizing evidence from published randomized controlled trials (RCTs).MethodsSeven databases were searched for relevant RCTs published up to 1 July 2024. Two investigators independently conducted the literature searches, data extraction, and quality assessment. Subgroup and sensitivity analyses were performed to address potential heterogeneity. Data analyses were conducted using RevMan 5.4 software.ResultThirty RCTs with a total of 3,931 participants were included in the study and analyzed. The results revealed that SFI significantly reduced major adverse cardiac events (MACEs) (RR = 0.34, 95% CI: 0.24 to 0.49, p < 0.05). In addition, SFI lowered creatine kinase-MB (CK-MB) (MD = −5.65, 95% CI: −9.55 to −1.76, p < 0.05) and improved left ventricular ejection fraction (LVEF) (MD = 6.2, 95% CI: 4.82 to 7.57, p < 0.05). Further reductions were observed in C-reactive protein (CRP) (MD = −6.17, 95% CI: −8.11 to −4.23, p < 0.05), malondialdehyde (MDA) (MD = −1.95, 95% CI: −2.08 to −1.83, p < 0.05), and endothelin-1 (ET-1) (MD = −12.27, 95% CI: −17.13 to −7.40, p < 0.05). The incidence of adverse events did not significantly differ between the EG and CG [RR = 0.74, 95% CI: 0.42 to 1.33, p = 0.32].ConclusionThis study suggests that SFI may be a promising alternative therapy for treating AMI without increasing the risk of adverse events. However, our findings may be limited by the quality of the existing studies. High-quality RCTs are needed to provide more robust evidence.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024567279.